The Wizard - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Wizard" by H. Rider Haggard is a novel published in 1896. Reverend Thomas Owen travels to south central Africa to convert the Amasuka tribe, known as the People of Fire. There he confronts Hokosa, chief of the Wizards, who demands he prove his God's power through dangerous trials by lightning. Set against the backdrop of British colonialism, this tale of faith and cultural collision unfolds through poison plots, magical contests, and ultimately sacrifice, as competing beliefs clash in dramatic fashion. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Wizard_(novel)
Release date is 2006-04-04
Produced by John Bickers; Dagny; David Widger
Keywords: Africa -- Fiction; Missionaries -- Fiction